Analysis of conditions favourable for small vertical axis wind turbines between building passages in urban areas of Sweden. Issue 5 (28th May 2017) - Awan, Muhammad Rizwan; Riaz, Fahid; Nabi, Zahid
Abstract : This paper presents the analysis of installing the vertical axis wind turbines between the building passages on an island in Stockholm, Sweden. Based on the idea of wind speed amplification due to the venture effect in passages, practical measurements were carried out to study the wind profile for a range of passage widths in parallel building passages. Highest increment in wind speed was observed in building passages located on the periphery of sland as wind enters from free field. Wind mapping was performed in the island to choose the most favourable location to install the vertical axis wind turbines (VAWT). Using the annual wind speed data for location and measured amplification factor, energy potential of the street was calculated. This analysis verified that small vertical axis wind turbines can be installed in the passage centre line provided that enough space is provided for traffic and passengers.